Intertrochanteric Osteotomies in Children and Adolescents: Principles of Proximal Femoral Deformity Correction. Issue 24 (15th December 2022) - Miller, Katherine E.; Mosca, Vincent S.; Blumberg, Todd J.
Abstract : Intertrochanteric osteotomies are used to correct a variety of congenital and acquired deformities of the proximal femur in children and adolescents. Varus, valgus, flexion, extension, or rotational osteotomies at the intertrochanteric level can be used to restore normal alignment of the proximal femur, increase congruency and stability of the hip joint, facilitate healing or remodeling of the femoral head and neck, redirect the articular surface, and improve functional limb position in the case of soft-tissue contractures. The steps necessary to assess proximal femoral deformity and plan the appropriate osteotomy are described along with indications and long-term considerations.